Scientifico! like Dad: On the Intergenerational Transmission of STEM Education in Italy - Diana Chise; Margherita Fort; Chiara Monfardini (Institute of Labor Economics (IZA), 2019)
We provide novel evidence on the existence and the extent of intergenerational transmission of STEM (Science, Technology, Engineering and Mathematics) education using a recent large administrative dataset of Italian graduates obtained from the Almalaurea data. Parental influence on two STEM educational outcomes (high school and university degree completion) is strong and, net of student's time-invariant unobserved heterogeneity, proves to be stronger at the stage of the educational career closer to labour market entry. At this stage, the influence of fathers outweighs the one of mothers and is larger for sons than for daughters. The documented STEM intergenerational transmission is not driven by liberal profession of parents for most of STEM fields, while it is for some non-STEM fields (economic and legal studies), consistently with the presence of entry barriers in some professions.
Keywords: J16; J24; I24; 330; gender; intergenerational transmission; parents; STEM